A rare case report of perioral sarcoidosis - S M Balaji; Preetha Balaji (Wolters Kluwer Medknow Publications, 2021)
The Rationale: Sarcoidosis is a multisystemic granulomatous disease of unknown aetiology that usually presents with systemic lesions including the skin. Isolated cutaneous lesions are very rare. Patient Details: We present a middle-aged female patient, a known systemic lupus erythematosus patient, in remission developing an isolated, single sarcoidosis lesion in the perioral labial mucosa. The lesion was a rapidly growing nodular lesion with a papillary surface near the philtrum of the upper lip. Diagnosis: A biopsy revealed that to be a granulomatous lesion with large multinucleated giant cells. Using a panel of tests, by excluding tuberculosis and establishing the immunoprofile, the diagnosis was established. Although infrequent, perioral and oral lesions may constitute the first signs of systemic sarcoidosis. Outcomes and Take-away Lessons: For this reason, the oral health care provider needs to be watchful and when there is a suspicion of sarcoidosis, systemic sarcoidosis must be included in the differential diagnosis of oral and perioral granulomatous lesions.